Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Terre(s) des femmes? - Institut de recherches et d'études féministes (FéminÉtudes, 1996)
Cette publication de 1996 aborde les identités et les théories postmodernes de la fin du XXe siècle en études féministes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; droits des femmes*; féminétudes; histoire et politique; intersectionnalité; militance; postmodernisme; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap

White privilege and male privilege: A personal account of coming to see correspondences through work in women's studies - McIntosh, Peggy (Wellesley College, Center for Research on Women, 1988)
Through work to bring materials and perspectives from Women's Studies into the rest of the curriculum, I have often noticed men's unwillingness to grant that they are overprivileged in the curriculum, even though they may grant that women are disadvantaged. Denials that amount to taboos surround the subject of advantages that men gain from women's disadvantages. These denials protect male privilege from being fully recognized, acknowledged, lessened, or ended.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discours dominant; intersectionnalité; privilèges; périodes historiques; racisme; ressource en ligne; régions géographiques; savoir expérientiel; sexisme; systèmes d'oppressions; états-unis

Framing feminism: art and the women's movement, 1970-1985 - Parker, Rozsika (Popular culture critical readers, 1987)
Feminism has been a major force in the reshaping of recent art. The women's movement has given new confidence to women who work in the visual arts; it has opened up new areas for art to deal with and challenged existing systems of values and imagery in the arts. In their comprehensive introduction, Rozsika Parker and Griselda Pollock provide a richly illustrated history of the British women's art movement, covering the major events and debates in feminist art practice which have taken place over the last fifteen years. They also examine the trends, the conflicts and the new directions of the 1980s in which issues of race, as well as gender, have necessarily become prominent. Griselda Pollock goes on to explore the place of feminist art in the context of post-modern culture, arguing that feminism is one of the most important and radical interventions in both modernism and post-modernism. --back cover.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; postmodernisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Dreams, Demands, and Desires : The Black, Antiwar, and Women’s Movements - Studio Museum in Harlem; Lippard, Lucy (Tradition and conflict images of a turbulent decade: 1963-1973, 1985)
Essay in a catalogue for an exhibition that is considered a key survey of how Black art was inspired or affected by the civil rights movement.
Keywords: 1900-1999; 1960-1969; 1970-1979; amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; représentation des femme*; régions géographiques; thématiques; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis